UGAMO MALIM DALAM DISKURSUS KEAGAMAAN DI HUTATINGGI KABUPATEN TOBA SAMOSIR - Lamahu, Arafat Iskandar (Jurnal Sosiologi Agama, 2020)
Although not an official status, adherents of the Malim teachings or Parmalim remained faithful in carrying out teachings originating from Debata Mulajadi Nabolon. Ugamo Malim is a growing religion in Batak land. In the development of Uugamo Malim, he passed various historical events which also influenced the formation of ugamo Malim's institution. This study aims to understand the side of the ugamo Malim religious dimension, and look at the discourse of ugamo Malim's development, and then look at the institutionalized process of Ugamo Malim. Ugamo Malim as a religion has its own way of expressing their religious practices that appear in Ugamo Malim's religious dimensions. The history of ugamo Malim's development shows the other side of the movement of the Paderi (Islam) forces and the Gospel preaching movement by the Rheinische Mission-Gesellschaft (RMG) (Christian) in the land of Batak. The application of the theory of involvement by the RMG and the Dutch East Indies Government in Batak land also had a major impact on the institutionalization of Ugamo Malim. Seeing developments in the Batak lands at that time, Raja Sisingamangaraja XII instructed Raja Mulia Naipospos to build Bale Pasogit in Hutatinggi, to replace the Batak religious building in extinct Bakkara which was burned down by the Dutch.